TAUHID SEBAGAI ESENSI PENDIDIKAN ISLAM: ANALISIS PEMIKIRAN ISMAIL RAJI AL-FARUQI - Nur Kholifatul Ummah; Ainur Rafik; Zainuddin Al Haj Zain (At Turots: Jurnal Pendidikan Islam, 2025)
Islamic education as an idea that contains basic views about humans and the relevance of humans on this earth is determined by their ability to seek and utilize knowledge for the good of humans. This study uses a literature review (Library Research) to determine a specific research theme related to Al-Faruqi's thoughts, such as monotheism, Islamization of knowledge, and Islamic education. After determining the theme, the next step is to find relevant information from various sources, such as books, scientific articles, academic journals, theses, and primary sources. This method allows researchers to explore Al-Faruqi's ideas without conducting more in-depth field .